The role of heavy reflux in pressure swing adsorption for industrial carbon capture - Jinbiao Luo; Hao Yuan; Yalou Guo; Shuangjun Li; Qingchuan Chen; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Bacteria–polysaccharide interfacial regulation by calcium alginate hydrogel capsules supports sulfate reduction in acidic water - Yujie Wang; Fangzhou Luo; Zhaoyue Yang; Zhenghua Liu; Huachan Lin; Xiyu Liu; Min Zhang; Guoping Jiang; Lei Zhou; Lechang Xu; Delong Meng; Qingyun Yan; et al. (Carbohydrate Polymers, 2026)

The relationship between micro-fragmentation mechanisms and macro-mechanical responses in granite residual soil - Bingxiang Yuan; Xiangwen Deng; Peng Luo; Xueqiang Yang; Jim Shiau; Xiaoyu Bai; Mayao Cheng; Guoping Lei; Junjie Zheng (Transportation Geotechnics, 2026)

The robotic revolution in biofouling management: Disruption, adaptation, and the future of antifouling industries - Heting Hong; Chengyi Luo; Guoping Hong (Regional Studies in Marine Science, 2025)

Unveiling the components, physiological functions and emerging trends of hydroxycinnamic acid amides in goji berry (Lycium) - Siyuan Wei; Yuying Wang; Shiyu Zhou; Shina Luo; Yunuo Lin; Ruixi Wang; Qinyue Jia; Tingting Feng; Guoping Zhao; Xuefeng Yin; Fangwei Yang (Food Research International, 2025)

The defect engineering design of COCN/L-CdS/Ni2P for promoting hydrogen energy generation from seawater coupling with photoreforming of plastics - Zhe Yin; Ziwen Wang; Jun Wang; Binglin Tang; Guoping Yu; Qiuyu Wang; Huanyu Chen; Kangzheng Li; Zhichao Zhang; Qingcheng Luo; Fuqin Zhang; Bo Lv (Fuel, 2025)

Trans-scale Evaluation of Strengthening of a Shale by Injecting Oil- and Water-Based Nanoparticle Suspensions - Yongkang Wu; Yucheng Li; Shengmin Luo; Meng Lu; Nancy Zhou; Yuanzhi Qu; Yuan Geng; Guoping Zhang (Rock Mechanics and Rock Engineering, 2025)

High temperature co-processing of basic oxygen furnace slag and blast furnace slag: Self-pulverization and reduction mechanism - Lan Huang; Shengli An; Fang Zhang; Jun Peng; Guoping Luo; Yuxin Chen; Yifan Chai (Process Safety and Environmental Protection, 2025)

Non-noble CeO2/CdS/NiS heterojunction for photoredox-catalyzed plastic waste selective synthesis and hydrogen production from natural seawater - Ziwen Wang; Qiuyu Wang; Zhe Yin; Man Zhang; Guoping Yu; Qingcheng Luo; Huanyu Chen; Binglin Tang; Kangzheng Li; Zhichao Zhang; Bo Lv (Fuel, 2025)

Insight into the effect of the ectoparasites on estimating the ontogenetic accumulation of trace and rare earth elements in fish: A case study of Mackerel icefish (Champsocephalus gunnari) - Di Luo; Zhihong Zheng; Guoping Zhu (Environmental Research, 2025)

Preparation of cementing material and recovery of iron resources using converter slag - Shuai Hao; Guoping Luo; Lin Wang; Shengli An; Yifan Chai; Wei Song (Process Safety and Environmental Protection, 2024)

Multiphase riveting structure constructed by slight molybdenum for enhanced P3/O3 layer-structured oxide cathode material - Hailong Ren; Xuan-Wen Gao; Dongrun Yong; Zhaomeng Liu; Xuanchen Wang; Guoping Gao; Hong Chen; Qinfen Gu; Wen-Bin Luo (Chemical Engineering Journal, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Highly efficient thermal decomposition of AP through intimately encapsulating in 3DOM CoFe2O4 spinel - Desheng Yang; Chaofei Bai; Fengdan Zhu; Chang Liu; Cheng Zhao Tu; Guoping Li; Yunjun Luo; Tianfu Zhang (Chemical Engineering Journal, 2024)

Mechanistic study on the promotion of Ca2+ leaching in steel slag through high-temperature solid waste modification - Dongfeng He; Liu Yang; Yinbo Luo; Hongbo Zhao; Guoping Liu; Zhanjun Wu (Environmental Science and Pollution Research, 2024)

Structural Control of the Getang Carlin-Type Gold Deposit in Southwest China - Guoping Zeng; Xinlu Hu; Diwei Luo; Jianzhong Liu; Shuzhen Yao; Yongjie Jin (Journal of Earth Science, 2024)

Unique ternary Pd/NH2-MIL-125/CdIn2S4 composite expands the absorption range of visible light and improves H2 evolution efficiency - Man Zhang; Kangzheng Li; Zhe Yin; Zhichao Zhang; Qingcheng Luo; Binglin Tang; Guoping Yu; Tianding Hu; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2024)

Simultaneous decontamination of phosphorus and bisphenol A from livestock wastewater with boehmite-modified carbon composite - Yaru Peng; Xiu Zhang; Yuan Luo; Azeem Muhammad; Guoping Yang; Kuok Ho Daniel Tang; Zengqiang Zhang; Yuan Xu; Menghao Li; Jintong Cui; Ronghua Li (Bioresource Technology, 2024)

The dysregulation of miRNAs in epilepsy and their regulatory role in inflammation and apoptosis - Guoping Xie; Huan Chen; Chan He; Siheng Hu; Xue Xiao; Qunying Luo (Functional & Integrative Genomics, 2023)
Epilepsy is a neurological disorder that impacts millions of people worldwide, and it is characterized by the occurrence of recurrent seizures. The pathogenesis of epilepsy is complex, involving dysregulation of various genes and signaling pathways. MicroRNAs (miRNAs) are a group of small non-coding RNAs that play a vital role in the regulation of gene expression. They have been found to be involved in the pathogenesis of epilepsy, acting as key regulators of neuronal excitability and synaptic plasticity. In recent years, there has been a growing interest in exploring the miRNA regulatory network in epilepsy. This review summarizes the current knowledge of the regulatory miRNAs involved in inflammation and apoptosis in epilepsy and discusses its potential as a new avenue for developing targeted therapies for the treatment of epilepsy.

Regulatory miRNAs, circRNAs and lncRNAs in cell cycle progression of breast cancer - Huan Chen; Guoping Xie; Qunying Luo; Yisha Yang; Siheng Hu (Functional & Integrative Genomics, 2023)

Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Sample Collection, DNA Extraction, and Library Construction Protocols of the Human Microbiome Studies in the International Human Phenome Project - Yetong Wang; Ruyi Zhang; Yanni Pu; Danqi Wang; Yanren Wang; Xuemei Wu; Yujie Pan; Chen Luo; Guoping Zhao; Zhexue Quan; Yan Zheng (Phenomics, 2023)

The Lnc-HOTAIR/miR122/PPARγ signaling mediated the occurrence and continuous development of alcohol-induced Osteonecrosis of the femoral head - Guoping Le; Mengting Lu; Li Li; Hanwen Luo (Toxicology Letters, 2023)

A self-assembled nanoporous polyelectrolytic interlayer for highly stable zinc metal anodes - Siyu Tian; Long Zhou; Wei He; Yafen Tian; Yue Zhou; Shiwen Wu; Ruda Jian; Kenneth J. Balkus; Tengfei Luo; Guoping Xiong (Chemical Engineering Journal, 2023)

Bio-inspired salt-fouling resistant graphene evaporators for solar desalination of hypersaline brines - Shiwen Wu; Siyu Tian; Ruda Jian; Long Zhou; Tengfei Luo; Guoping Xiong (Desalination, 2023)

The role of melatonin in tomato stress response, growth and development - Qiaoli Xie; Yu Zhang; Yingxia Cheng; Yanling Tian; Junjie Luo; Zongli Hu; Guoping Chen (Plant Cell Reports, 2022)

Big Data Nanoindentation and Analytics Reveal the Multi-Staged, Progressively-Homogenized, Depth-Dependent Upscaling of Rocks’ Properties - Shengmin Luo; Daeyoung Kim; Yongkang Wu; Yucheng Li; Dongfang Wang; Jinliang Song; Don J. DeGroot; Guoping Zhang (Rock Mechanics and Rock Engineering, 2021)

Spatial and temporal variations of the diatom communities in megacity streams and its implications for biological monitoring - Xiang Chen; Weiqi Zhou; Guoping Luo; Pei Luo; Zhi Chen (Environmental Science and Pollution Research, 2020)

Characterization of Shale Softening by Large Volume-Based Nanoindentation - Yunhu Lu; Yucheng Li; Yongkang Wu; Shengmin Luo; Yan Jin; Guoping Zhang (Rock Mechanics and Rock Engineering, 2020)

Regulating effect of CBF on memory in cognitively normal older adults with different ApoE genotype: the Alzheimer’s Disease Neuroimaging Initiative (ADNI) - Junyang Wang; Guoping Peng; Ping Liu; Xufei Tan; Benyan Luo (Cognitive Neurodynamics, 2019)

MicroRNA let-7e Is a Potential Circulating Biomarker of Acute Stage Ischemic Stroke - Guoping Peng; Yuan Yuan; Shanshan Wu; Fangping He; Yewen Hu; Benyan Luo (Translational Stroke Research, 2015)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

Centrifugal forces within usually-used magnitude elicited a transitory and reversible change in proliferation and gene expression of osteoblastic cells UMR-106 - Juan Li; Lingyong Jiang; Ga Liao; Guoping Chen; Ying Liu; Jun Wang; Yi Zheng; Songjiao Luo; Zhihe Zhao (Molecular Biology Reports, 2009)

The role of extracellular matrix, integrins, and cytoskeleton in mechanotransduction of centrifugal loading - Juan Li; Zhihe Zhao; Jun Wang; Guoping Chen; Jingyuan Yang; Songjiao Luo (Molecular and Cellular Biochemistry, 2008)

Osteoblast cytoskeletal modulation in response to compressive stress at physiological levels - Juan Li; Guoping Chen; Leilei Zheng; Songjiao Luo; Zhihe Zhao (Molecular and Cellular Biochemistry, 2007)